Critical competition period between Carrot (Daucus carota L.) and weeds - Dotor R., Mónica Yadira; González Mendoza, Leonardo Ariel; Morillo C., Ana Cruz (Revista de Ciencias Agrícolas, 2018)
Weeds are one of the phytosanitary problems that affect crop’s productivity. The critical period of competition (PCC) allows to predict the level of interference of weeds on the crop. The objective of this investigation was to determine the PCC between carrot and weeds or other accompanying plants, in the municipality of Ventaquemada, department of Boyacá. A completely randomized blocks, with 12 treatments and four repetitions, was used. It included a group of treatments free of weeds for 10, 20, 30, 40 and 50 days, at the end each the weeds growth was allowed, so that the crop was first free and then in competition (FC). The second group of treatments allowed the initial competition between weeds and the crop, for the same period of first group at the end of each time period the weeds were removed. The largest amount of carrots plants was obtained in the free weeds plot during 50 days after emergence. The highest yield was attained in the free weeds treatment throughout the crop cycle (5810g m-2). It was 2252g higher than the production obtained at the critical point of competition. In general, the critical period of competition in carrot was thorough 20 to 45 days after crop emergence.